Calculating the grain boundary inclination of voxelated grain structures using a smoothing algorithm. (September 2022) - Yang, Lin; Hilty, Floyd; Muralikrishnan, Vivekanand; Silva-Reyes, Kenneth; Harley, Joel B.; Krause, Amanda R.; Tonks, Michael R.
Graphical abstract: Abstract: We have developed a flexible method for calculating the grain boundary (GB) inclinations of voxelated grain structure data using smoothing algorithms. We compared the performance of four algorithms: the linear interpolation, Allen–Cahn, level-set, and vertex algorithms. We assessed their accuracy using 2D and 3D cases with known inclinations. The vertex algorithm provided the best balance between accuracy and efficiency for 2D structures while the linear interpolation algorithm provided the best balance for 3D structures. We compared the GB inclinations calculated using our smoothing method on a 3D high energy X-ray diffraction microscopy (HEDM) dataset to those determined by meshing the GBs. The two approaches determined similar GB plane distributions, though they varied significantly at triple junctions. Finally, the smoothing method was demonstrated for two sources of 3D voxelated grain structures: HEDM data and results from Monte Carlo Potts grain growth simulations.